The Brothers Grimm - Gilliam, Terry; Miramax Films (The Brothers Grimm United States, 2005)
The story follows the Grimm brothers, traveling con artists who encounter a real magical curse in a haunted forest village, forcing them to confront supernatural forces and become the heroes of their own legend.
A fantasy adventure inspired by the lives of the famous fairy-tale authors Jacob and Wilhelm Grimm.
Rated PG-13.
Keywords: Fairy tales; Brothers